Lifestyle components of the global oldest old assessed as effective nonpharmacologic strategies to maintain lifelong cognitive and functional health - Cécil J.W. Meulenberg (Exercise and Quality of Life)
Longevity and high quality of life are amongst the most desired traits of humanity. However, the incidences of non-communicable diseases are rising, while sedentary lifestyles and malnutrition are more common than ever, and in general both functional and cognitive health is declining. Besides the concurrent costs to provide healthcare for such an aging population are dramatically increasing and depend on pharmacological treatment. There is an urgent need to raise awareness for cost-saving healthier customs and to adjust lifestyles. From specific geographic areas around the globe, where its citizens tend to grow (very) old, that is over 100 years of age (indicated as ‘oldest old’), without the obvious health-deficits, the so-called blue zones, lifestyle factors have been identified, or will be proposed, and taken as candidate for nonpharmacologic approaches to improve general health. This paper will summarize scientific studies focussing on cardiovascular and cognitive health benefits induced by: Physical activity through exercise, light to moderate intensity, and nonexercise outdoors activities; Nutrition through the Mediterranean diet and the incidence of neurodegeneration; Cognitive engagement through cognitive-motor exercises, language usage, and meditation; and finally: Sleep. The identified denominators are reviewed through various scientific studies regarding substantiated healthinducing effects. Adherence to such nonpharmacologic lifestyles is eventually a personal choice, and for governments to take notice of, and to include in policies.